Deciphering maize resistance to late wilt disease caused by Magnaporthiopsis maydis: agronomic, anatomical, molecular, and genotypic insights - Abdelghany, Walaa R.; Elsharkawy, Mohsen M.; Abdelkawy, Ramy N. F.; Omara, Reda I.; Abdelaal, Khaled; Abbas, Abeer H.; Hozzein, Wael N.; Essa, Tarek; ALkhalifah, Dalal Hussain; Abou Tabl, Ayman H. (Frontiers in Plant Science, 2025)
IntroductionMagnaporthiopsis maydis, the causal agent of late wilt disease (LWD), poses a significant threat to maize production by reducing grain yield and quality. Identifying and developing resistant genotypes adapted to different environments is essential for sustainable crop improvement.MethodsFifteen maize genotypes were evaluated for their response to LWD across three growing seasons at two experimental locations—Gemmeiza and Sids. Disease incidence, agronomic performance, anatomical features, and antioxidant enzyme activities were assessed. Gene expression analysis of PR1 and PR4 was conducted using RT-qPCR. Genotype × environment interaction (GEI) was analyzed using combined ANOVA and the additive main effects and multiplicative interaction (AMMI) model.ResultsSignificant differences were observed among genotypes, environments, and their interactions (GEI) for disease incidence and yield-related traits (p < 0.05). AMMI analysis confirmed substantial GEI effects on DI% and hundred kernel weight. Genotypes TWC1100, SC30K9, and SC2031 consistently showed the lowest disease incidence and the highest resistance rating index (RRI > 8.3) across both locations, while the susceptible check Boushy recorded the highest DI% and lowest RRI. TWC1100 and SC30K9 also achieved the highest kernel weights at Gemmeiza (42.8 g and 41.5 g, respectively). Stability analysis using AMMI stability value (ASV) identified TWC1100, SC30K9, TWC324, and SC130 as the most stable genotypes. Biochemical analysis revealed that resistant genotypes exhibited higher peroxidase activity and lower electrolyte leakage. Anatomical examination showed superior root structure in resistant genotypes, particularly SC2031. Molecular analysis confirmed the upregulation of PR1 and PR4 genes post-infection, with TWC1100 showing robust expression, while Boushy exhibited minimal gene activation.DiscussionThe integration of agronomic, anatomical, biochemical, and molecular analyses revealed promising maize genotypes with enhanced resistance to late wilt disease (LWD) and stable performance across diverse environments. These findings highlight the potential of these genotypes as valuable candidates for inclusion in breeding programs targeting improved disease resistance and yield stability under varying environmental conditions.